A patchy response: the dangers of not keeping our systems secure. (January 2015) - Mansfield-Devine, Steve
Abstract : Malware is still rampant, and most of it depends on victims running outdated software on their systems. If all our computers were fully patched with the latest updates as soon as they appear, it would create a largely sterile environment as far as malware is concerned. So why doesn't this happen? In this interview, we spoke with Gavin Millard, EMEA technical director at Tenable Network Security. Keeping track of the vulnerabilities in your systems has never been easy, and timely patching is important if you want to prevent malicious people exploiting flaws in the systems and software you use. But with today's highly complex IT environments, it can be tricky to know which vulnerabilities apply to you. In this interview with Gavin Millard of Tenable Network Security, we discover how continuous monitoring, linked to effective remediation processes, is the only way to ensure you reduce the risk to your organisation to acceptable levels.